2021
DOI: 10.14740/jocmr4551
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cervical Muscles Morphology in the Surgical Treatment of Degenerative Disc Disease: Clinical Correlations Based on Magnetic Resonance Imaging Studies

Abstract: Cervical spine musculature still remains a less studied component of the cervical spine anatomical compartments, although it plays a significant role in the mobility of the head and the preservation of cervical spine alignment. The goal of this study was to extract any significant information from the literature regarding the role of cervical spine muscles morphology in the outcome of surgically treated patients for degenerative disc disease (DDD) based on preoperative magnetic resonance imaging (MRI) studies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 60 publications
1
4
1
Order By: Relevance
“…Additionally, in agreement with studies examining paraspinal muscle ( 4 , 11 , 25 ), our findings reveal that FI is more prevalent in elderly patients. In contrast to earlier findings ( 26 ), however, no evidence of association between FI and gender or BMI was detected in our research.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Additionally, in agreement with studies examining paraspinal muscle ( 4 , 11 , 25 ), our findings reveal that FI is more prevalent in elderly patients. In contrast to earlier findings ( 26 ), however, no evidence of association between FI and gender or BMI was detected in our research.…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study, improved clinical outcomes reflected by VAS, JOA score, and NDI demonstrated that HS effectively ameliorated neurological symptoms, consistent with previous findings reported by Scott-Young et al (27). More importantly, numerous studies in the past linked muscle FI to postoperative pain or neurological deficits, particularly following lumbar spine and posterior cervical surgery (4,13,26). In a recent systematic review of 873 patients, Jermy et al recently identified a link between a low FI and greater improvement in low back pain and disability following lumbar spine surgery (12).…”
Section: Fsua Of Fusion Level (°)supporting
confidence: 90%
See 3 more Smart Citations